"The tree was there first" – using an everyday ecological dilemma to explore the personal orientations of secondary school students in environmental decision-making. Issue 1 (2nd January 2021) - Altmeyer, Stefan; Dreesmann, Daniel
Abstract: Studies have repeatedly shown that the goals of environmental education are as indispensable as they are difficult to achieve. In particular, the discrepancy between environmental awareness and everyday actions seems to be particularly large and strongly dependent on personal factors. Against this background, the authors argue that the evaluation of everyday environmental situations should be considered and different personal orientations should be addressed. In a study among more than 1, 100 secondary school students in Germany and Austria, an instrument was developed and tested that focuses on an everyday environmental dilemma and its evaluation. The use of this instrument identified five types of student orientations, each of which was accompanied by a typical evaluation pattern. The authors conclude that the instrument is applicable to educational practice as classroom tool, to identify students' environmental orientations and develop teaching programmes that can deal with these personal predispositions in an appropriate and differentiating manner.